Role of Deficit Irrigation in Sustaining Wheat and Maize Cultivation Under Harsh Climatic Conditions in Iraq (Journal of Engineering, 2026)
Water scarcity and climate variability threaten the sustainable production of strategic crops such as wheat and maize in arid regions like Iraq. Conventional irrigation methods are increasingly insufficient to satisfy crop water requirements due to rising evapotranspiration and reduced effective rainfall. Therefore, Deficit Irrigation (DI), which involves applying water below full crop water requirements, has become an important strategy for improving water use efficiency. This paper aimed to evaluate irrigation water requirements and crop responses to different DI levels in arid conditions, selecting the Al-Raed Research Station in Iraq as the study area. Climatic data were analyzed using the CROPWAT 8 model to estimate crop evapotranspiration, effective rainfall, net irrigation requirement, and gross irrigation requirement at full irrigation and DI levels ranging from 5% to 25% in steps of 5%, with 5% across four growth stages. The results showed that wheat had relatively low sensitivity to water deficit, with no yield reduction at DI5% during most growth stages and a maximum reduction of 2.0% at DI25%, mainly during the mid-season stage. In contrast, maize was more sensitive to water deficits, particularly during development and mid-season, with yield reductions of 4.3% and 4.0%, respectively, under DI25%. However, under DI5%, maize showed only minor yield reduction, not exceeding 0.3%. Overall, DI5% can be recommended during the initial and development stages for both crops due to their low water demand and limited sensitivity to water stress during early growth.